What Do the EFL Pre-Service Teachers Say about Teacher Autonomy? - Humaera, Isna; Afrizal, Muh; Rezki, Anita (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
This study delves into the exploration of EFL pre-service teachers' perceptions of teacher autonomy during field teaching practice, drawing on reflective insights from ten participants in the English Education Department. The qualitative investigation centers on the multifaceted concept of teacher autonomy, encompassing dimensions like professional development, freedom from external control in teaching, and the capacity for self-directed instructional approaches. Employing a thematic analysis method, the research underscores a prevalent positive inclination among pre-service teachers toward the application of teacher autonomy. Key themes identified include the influence of the public sphere, the pedagogical creative teaching process, organizational dynamics, proficiency in content curriculum knowledge, insights from students' reflections, and the promotion of learner autonomy. The study emphasizes implications for teacher educators and institutions, stressing the significance of the long-term development of pre-service teachers for the sustained success of educational programs. It advocates for a robust understanding of teacher autonomy among pre-service teachers and the provision of ongoing support to maintain motivation and efforts in exercising autonomy. While offering valuable insights, the study acknowledges limitations, notably the reliance on qualitative data from reflective accounts, necessitating caution in generalizing findings. This would provide a more comprehensive understanding of the nuanced relationship between teacher autonomy and professional development among pre-service teachers.